Suzuki-Miyaura Cross-Coupling of Potassium Dioxolanylethyltrifluoroborate and Aryl/Heteroaryl Chlorides - Fleury-Brégeot, Nicolas (2013)
[Image: see text] A robust and efficient protocol for the introduction of the dioxolanylethyl moiety onto various aryl and heteroaryl halides has been developed, providing cross-coupling yields up to 93%. Copper-catalyzed borylation of 2-(2-bromoethyl)-1,3-dioxolane with bis(pinacolato)diboron followed by treatment with potassium bifluoride provides the key organotrifluoroborate reagent.